A Case of Successful Allogeneic Hematopoietic Stem Cell Transplantation in a Severely Underweight Patient with Aplastic Anemia - Lilija Banceviča; Andrius Žučenka (Case Reports in Hematology)
Allogeneic hematopoietic stem cell transplantation (alloHSTC) is considered definitive and the most effective treatment for young patients diagnosed with severe aplastic anemia. Low body mass index (BMI) is known to be associated with poorer outcomes in stem cell transplantation and higher mortality risks. Malnutrition negatively affects the patient’s ability to mobilize stem cells, therefore reducing patients’ stem cell production, although the patient’s nutritional status improvement with enteral and parenteral nutrition may reduce the risks of stem cell graft failure and graft-vs-host disease (GVHD) occurrence. The present report demonstrates a severely underweight patient with aplastic anemia and a BMI of 11 kg/m2 who was unsuccessfully treated with immunosuppressive therapy followed by alloHSTC.